The Sikh next door: an identity in transition - Singh, Manpreet J. (Bloomsbury Publishing, 2020)
Preface -- Acknowledgements -- Introduction - Beyond the Normative: Re-Contextualising Sikhs -- 1. Nudged Out of the Narrative: The Trader/Professional Sikh -- 2. Evolving Urban Profiles: From the Village to the City -- 3. They Are Not Like Us: Sikhs in Other Cultural Settings -- 4. Finding New Anchors: Sikh Identity in Foreign Lands -- 5. Process of Becoming: The Sikh Woman -- 6. Images and Stereotypes: Exploring the Impetus -- Conclusion - Continuity in Change: A Centre that Holds -- Glossary -- Bibliography -- Index.